Aspek Motivasi Novel Laskar Pelangi Karya Andrea Hirata dan novel negeri 5 menara karya a. Fuadi : kajian Interteks Dan Implementasinya Dalam Pembelajaran Sastra Di Sma - Setyastuti, Susilo; , Prof. Dr. Ali Imron Al Ma'ruf, M. Hum; , Dr. Nafron Hasjim (2016)
This study has four objectives. (1) describe the structure that builds novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. ceremony. (2) Describe the motivational aspects contained in novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. ceremony. (3) Describe the intertextual relationship motivational aspects contained in novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. ceremony. (4) Describe the implementation of the research results novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. Fuadi as learning materials Indonesian literature in MA. Metode research used in assessing novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. Fuadi is descriptive qualitative method with embedded strategies and case study (case study spikes). The object of this study is the motivational aspect in novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. ceremony. The validity of the data using triangulation data. Data were analyzed using data analysis techniques are heuristic and hermeneutic reading. Based on the research that has been done, it can be concluded (1) the structure of novel Laskar Pelangi by Andrea Hirata and Negeri 5 Menara works of A. Fuadi covers, themes, characterizations, plot, and setting. Judging from the structure, both the novel have similarities and differences. Equation is located on the second theme of the novel have the same theme of education. The second difference lies in the novel aspects of characterization, plot, and setting. (2) Aspects of motivation contained in the form of a second novel aspect of achievement motivation in learning and achievement in business, power motivation, and motivation relationships. (3) The relationship intertextual aspects of motivation, novel Laskar Pelangi is a text hipogram that transform aspects of achievement motivation, motivational aspects of power, and motivational aspects in relation to Negeri 5 Menara novel as text transformation. (4) Implementation of motivation in the novel aspects and novel Laskar Pelangi Negeri 5 Menara as teaching material in high school literature is able to meet the criteria as a decent literary teaching materials in teaching literature in high school students. Implementation of the results of the motivational aspects can form language skills, improve cultural knowledge, develop creativity and taste as well as to support the formation of character and follow the changing times.